Production of Hexanol as the Main Product Through Syngas Fermentation by Clostridium carboxidivorans P7 - Oh, Hyun Ju; Ko, Ja Kyong; Gong, Gyeongtaek; Lee, Sun-Mi; Um, Youngsoon (Frontiers in Bioengineering and Biotechnology, 2022)
The production of hexanol from syngas by acetogens has gained attention as a replacement for petroleum-derived hexanol, which is widely used in the chemical synthesis and plastic industries. However, acetogenic bacteria generally produce C2 compounds (e.g., acetate and ethanol) as the main products. In this study, the gas fermentation conditions favorable for hexanol production were investigated at different temperatures (30–37℃) and CO gas contents (30–70%) in batch gas fermentation. Hexanol production increased from 0.02 to 0.09 g/L when the cultivation temperature was lowered from 37℃ to 30℃. As the CO content increased from 30% to 70%, the CO consumption rate and hexanol production (yield, titer, and ratio of C6 compound to total products) increased with the CO content. When 70% CO gas was repeatedly provided by flushing the headspace of the bottles at 30℃, the total alcohol production increased to 4.32 g/L at the expense of acids. Notably, hexanol production (1.90 g/L) was higher than that of ethanol (1.20 g/L) and butanol (1.20 g/L); this is the highest level of hexanol produced in gas fermentation to date and the first report of hexanol as the main product. Hexanol production was further enhanced to 2.34 g/L when 2 g/L ethanol was supplemented at the beginning of 70% CO gas refeeding fermentation. Particularly, hexanol productivity was significantly enhanced to 0.18 g/L/day while the supplemented ethanol was consumed, indicating that the conversion of ethanol to acetyl-CoA and reducing equivalents positively affected hexanol production. These optimized culture conditions (gas fermentation at 30℃ and refeeding with 70% CO gas) and ethanol supplementation provide an effective and sustainable approach for bio-hexanol production.